2019
DOI: 10.1101/546069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditional activation of immune-related signatures and prognostic significance: a pan-cancer analysis

Abstract: 43An immune active cancer phenotype typified by a T helper 1 (Th-1) immune response has 44 been associated with increased responsiveness to immunotherapy and favorable prognosis 45 in some but not all cancer types. The reason of this differential prognostic connotation remains 46 unknown. Through a multi-modal Pan-cancer analysis among 31 different histologies (9,282 47 patients), we demonstrated that the favorable prognostic connotation conferred by the 48 presence of a Th-1 immune response was abolished i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…A higher mutation burden in cancer has been associated with an increased abundance of neoantigens, which can elicit immune responses and potentially lead to favorable responses to immunotherapy in types of cancer (Tran et al, 2017;Roelands et al, 2020;Huang et al, 2021). Our results showed that MUC4, AHNAK2, AHNAK, FLG2, MUC5AC, MUC3A, and MUC17 were the most common alterations in PGs.…”
Section: Discussionmentioning
confidence: 61%
“…A higher mutation burden in cancer has been associated with an increased abundance of neoantigens, which can elicit immune responses and potentially lead to favorable responses to immunotherapy in types of cancer (Tran et al, 2017;Roelands et al, 2020;Huang et al, 2021). Our results showed that MUC4, AHNAK2, AHNAK, FLG2, MUC5AC, MUC3A, and MUC17 were the most common alterations in PGs.…”
Section: Discussionmentioning
confidence: 61%
“…The cancer survival analysis with TCGA data was performed using UCSC XENA (https://xena.ucsc.edu) and for that with the gene expression array data was performed using KM plotter (http://kmplot.com) (34). Correlation between CCL5 and markers of stemness (cancer stem cells and normal stem cells) and epithelial to mesenchymal transition (EMT) markers, was performed by using a normalized RNA matrix, described elsewhere (35). The selection of markers was based on current literature (36).…”
Section: In Silico Analysis Of Ccl5 Gene Expressionmentioning
confidence: 99%
“…These tumor-type-specific differences might be due to differences in the underlying oncogenic dysregulations. For instance, we recently demonstrated that the prognostic value of Th1 immune infiltration is dependent on the activation status of specific oncogenic processes such as proliferation and TGF-B signaling, even within the same cancer type (Bertucci et al 2018;Roelands et al 2019).…”
Section: Introductionmentioning
confidence: 99%